Neandertal-early modern human interactions in Europe and the assimilation model of modern human origins - Smith, Fred. H. (Array, 2003)
Chronological evidence indicates that Neandertals survived well into OIS 2 (ca. 28 ka) in parts of Central Europe, Iberia and perhaps Eastern Europe. The earliest skeletal remains of modern humans in Europe are dated to ca. 35 ka at Mladec (Czech Republic) and ca. 32 ka at Vogelherd (Germany). Thus there is evidence of temporal overlap of populations in Central Europe. At Vindija (Croatia) there is evidence of a cultural assemblage combinig Middle and Upper Paleolithic types, and there are indications in various sites that late Neandertals developed tools and other items that seem similar to those of early modern people. This may well suggest contact between these peoples, and the presence of certain anatomical details in early modern Europeans indicates Neandertal biological contributions. The combined biocultural data support a model of assimilation of Neandertals into the early modern populations of Europe.